Radiopurity of CaWO4 crystals for direct dark matter search with CRESST and EURECA - Muenster, A; Sivers, M; Angloher, G; Bento, A; Bucci, C; Canonica, L; Erb, A; Feilitzsch, F; Gorla, P; Guetlein, A; Hauff, D; Jochum, J; et al. (Institute of Physics Publishing, 2014)
The direct dark matter search experiment CRESST uses scintillating CaWO4 single crystals as targets for possible WIMP scatterings. An intrinsic radioactive contamination of the crystals as low as possible is crucial for the sensitivity of the detectors. In the past CaWO4 crystals operated in CRESST were produced by institutes in Russia and the Ukraine. Since 2011 CaWO4 crystals have also been grown at the crystal laboratory of the Technische Universität München (TUM) to better meet the requirements of CRESST and of the future tonne-scale multi-material experiment EURECA. The radiopurity of the raw materials and of first TUM-grown crystals was measured by ultra-low background γ-spectrometry. Two TUM-grown crystals were also operated as low-temperature detectors at a test setup in the Gran Sasso underground laboratory. These measurements were used to determine the crystals' intrinsic α-activities which were compared to those of crystals produced at other institutes. The total α-activities of TUM-grown crystals as low as 1.23±0.06 mBq/kg were found to be significantly smaller than the activities of crystals grown at other institutes typically ranging between ∼ 15 mBq/kg and ∼ 35 mBq/kg. © 2014 IOP Publishing Ltd and Sissa Medialab srl.